(E)-3-[4-(Dodecyloxy)phenyl]-1-(2-hydroxyphenyl)prop-2-en-1-one - Zainab, Binti Ngaini; Ibrahim, Bin Abdul Razak; Fun, Hoong-Kun; Siti Muhaini, Binti Haris Fadzillah; Hasnain, Bin Hussain (International Union of Crystallography, 2009)
In the title compound, C27H36O3, the asymmetric unit consists of two crystallographically independent molecules. The aromatic rings form dihedral angles of 17.1 (2) and 17.6 (2) in the two molecules. In both molecules, the enone groups adopt an s–cis conformation and the alkoxyl chains are in trans conformations curving out of the zigzag plane. Intramolecular O—HO hydrogen bonds involving the keto and hydroxy groups generate S(6) ring motifs. The molecules are stacked alternately in a head-to-tail fashion along the a axis and the crystal structure is stabilized by weak C—H interactions. The crystal studied was a non-merohedral twin, the ratio of components being 0.788 (2):0.212 (2).